Defining Clinically Relevant Cerebral Hemorrhage After Thrombolytic Therapy for Stroke: Analysis of the NINDS-tPA Trials - Rao, Neal Matsumori (2014)
BACKGROUND AND PURPOSE: Several definitions have been proposed to distinguish clinically relevant from incidental cerebral hemorrhagic transformation after thrombolytic therapy for acute ischemic stroke. We investigated which definition best identifies cerebral hemorrhages that alter long-term functional outcome in The National Institute of Neurological Disorders and Stroke (NINDS) tPA Trials. METHODS: We analyzed four candidate hemorrhage definitions for which The NINDS tPA Trials public data set had relevant data. For each, we identified tPA-treated patients having that hemorrhage type and compared their actual functional outcomes at 90 days to their predicted outcomes had they not received tPA and not had the hemorrhage. Projected outcomes without tPA were based on a 17 variable prognostic model derived from The NINDS tPA Trials placebo group. RESULTS: Among the 312 patients treated with IV tPA, 33 (10.6%) experienced any radiologic intracerebral hemorrhage within 36 hours of treatment, 16 (5.1%) a radiologic parenchymal hematoma, 20 (6.4%) an NINDS defined symptomatic intracerebral hemorrhage (SICH), 12 (3.8%) an ECASS 2 defined SICH, and 6 (1.9%) a modified (m)SITS-MOST defined SICH. The ECASS2 and mSITS-MOST definitions identified the largest hemorrhage-related change in 90 day modified Rankin Scale scores (2.26–0.32=1.94, p=0.0001 and 2.81–0.63=2.18, p=0.0002 respectively). These definitions also distinguished the largest hemorrhage-related change in 90 day mortality (64.7%–7.6%=57.1%, p=0.0004 for ECASS2 and 68.4%–19.5%=48.9%, p=0.0152 for mSITS-MOST). CONCLUSIONS: The ECASS 2 and mSITS-MOST SICH definitions, which combine radiologic features and occurrence of substantial early neurologic deterioration, best identify tPA hemorrhages that alter final patient outcome.